(untitled) (Journal of Asian Development Studies, 2025)
This study examined how artificial intelligence reshaped financial decision-making and market dynamics within the emerging paradigm of intelligent finance. Drawing on a qualitative synthesis of recent journal research, the study explored the integration ofAI into trading, credit assessment, portfolio management, fraud detection, and risk governance. The findings showed that AI-driven systems enhanced predictive accuracy, analytical depth, and operational responsiveness by enabling financial institutions toprocess vast, complex datasets. These developments had supported improved forecasting, more granular borrower evaluation, and real-time risk surveillance. However, the study had also revealed that the benefits of AI adoption were closely interlinked with emerging challenges related to algorithmic opacity, fairness, governance, and systemic fragility. Widespread reliance on similar machine-learning models created the risk of synchronised behaviours and procyclical dynamics during periods of stress, while the use of alternative data raised ethical concerns around discrimination and accountability. The study concluded that the value of AI in finance depended not only on technological progress but also on the strength of regulatory oversight, model-governance structures, and human expertise supporting AI deployment. Intelligent finance was therefore best understood as a socio-technical transformation rather than a purely technological shift. The study recommended that financial institutions embed transparency, explainability, and fairness testing into AI implementation to ensure that innovation contributed to stability, inclusion, and ethical financial practice.